2016 Wireless Days (WD) 2016
DOI: 10.1109/wd.2016.7461487
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of UAV-mounted access points according to spatial user locations in two-tier cellular networks

Abstract: Abstract-We envision small cells mounted on unmanned aerial vehicles, to complement existing macrocell infrastructure. We demonstrate through numerical analysis that clustering algorithms can be used to position the airborne access points and select users to offload from the macrocells. We compare the performance of these deployments against equivalent simulated picocell deployments. We demonstrate that due to their ability to position themselves around exact user locations while maintaining a direct line-of-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 14 publications
0
90
0
Order By: Relevance
“…K-means clustering is a heuristic algorithm which partitions a given set of points in space into cells of approximately equal size and finds the centroid of the cells. In our previous work [17] we have demonstrated how this algorithm can be used to optimally position UAVs around known user locations. For the low UAV density scenario in Fig.…”
Section: B Uav Placement Comparisonmentioning
confidence: 99%
“…K-means clustering is a heuristic algorithm which partitions a given set of points in space into cells of approximately equal size and finds the centroid of the cells. In our previous work [17] we have demonstrated how this algorithm can be used to optimally position UAVs around known user locations. For the low UAV density scenario in Fig.…”
Section: B Uav Placement Comparisonmentioning
confidence: 99%
“…To obtain the numerical results at the medium height, we choose to analyze UAVs at the height of 50m and 100m, which are the most practical cases in reality. For the high-altitude model, the relative parameters are: A L = 10.38, A NL = 14.54, α L = 2.09, α NL = 3.75 [4], [13]. For the low-altitude model, path loss parameters are: A L = 10.34, A NL = 13.11, α L = 2.42, α NL = 4.28 [11].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Positions of UAV-BSs were modeled as a 3D Poisson Point Process (3D-PPP) distribution with a limited height in [1], but the analysis in [3] showed that the flexible height of UAV is not as helpful as a well-chosen fixed altitude. In [4], UAV-mounted mobile base stations were The work of Y.-C. Liang is funded by National Natural Science Foundation of China under Grants 61571100, 61631005 and 61628103. deployed in a fixed altitude and placed along an optimal trajectory to cover as much as user equipment (UE) whose locations are already known in a given area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…al., [78] and Galkin et. al., [79], but instead of brute force search, they employed genetic algorithm and K-means clustering, respectively, to solve the optimization problem.…”
Section: A Placement Optimization For Aerial Bssmentioning
confidence: 99%